2020
DOI: 10.1155/2020/7047189
|View full text |Cite
|
Sign up to set email alerts
|

Road Safety Challenges in Sub-Saharan Africa: The Case of Ghana

Abstract: The importance of road safety in the developmental agenda of a country cannot be overemphasized. It is essential for effective socioeconomic development. However, several countries in the developing world are confronted by several challenges relating to road safety, which are inadequately investigated. These challenges further aggravate the already heavily burdened health-care systems. The aim of this study is, therefore, to determine and analyse road safety issues in Ghana aimed at contributing to national po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…As shown in Table 6, the most challenging factor remains the first criterion C1 (road safety is not a political priority) with a value of 0.349. Our findings are in accordance with the previous studies of Small (2014) and Odonkor et al (2020) which indicate that the absence of political concern, interest, and priority is the main shortcoming of road safety management in Africa. The least significant criterion remains the third criterion C3 (little coordination between relevant government bodies).…”
Section: Resultssupporting
confidence: 93%
“…As shown in Table 6, the most challenging factor remains the first criterion C1 (road safety is not a political priority) with a value of 0.349. Our findings are in accordance with the previous studies of Small (2014) and Odonkor et al (2020) which indicate that the absence of political concern, interest, and priority is the main shortcoming of road safety management in Africa. The least significant criterion remains the third criterion C3 (little coordination between relevant government bodies).…”
Section: Resultssupporting
confidence: 93%
“…Paradoxically, SSA countries have poor road systems, which contribute to the burden of road traffic accidents [ 17 ]. The non-adherence of road traffic laws further compounds the burden of road traffic accidents in SSA [ 18 ]. SSA governments and stakeholders have invested in road transportation infrastructure and developed campaigns to increase the dissemination and adherence to road traffic rules [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…This immensely exerts significant pressure on the road which consequently lead to road indiscipline. Studies (Coleman 2014;Odonkor et al 2020) have shown that road indiscipline by drivers is considered as one of the leading causes of RTAs in major cities. Based on 2016 data, the total road fatalities hit 1,802 to 70% of the deaths falling between the ages 15-64 years (World Bank 2020).…”
Section: Minimise Road Accidentsmentioning
confidence: 99%